KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI PROGRAM LINEAR MELALUI TAHAPAN NEWMAN - Fachis, Choirul; Azizah, Dewi; Hidayah, Nurina (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The purpose of this article is to describe students' problem-solving abilities in completing linear programs through the Newman stages. This article uses qualitative. Data collection was obtained from the method of setting, testing, and interviewing. There are 36 students in class IX PS 2 as the subject of this article. The subject's abilities are categorized as high, medium, and low. Descriptive analysis was obtained from 9 students who represented each level. Test the validity of the data by triangulation. The results of the analysis obtained an average problem-solving ability using the Newman stage, namely the ability to read problems 85.6% classified well, the ability to solve problems 80% classified well, the ability to transform 82.59% classified well, the ability to process 73.3% classified good, the ability to solve answers 67.7% classified sufficiently. Of the 8 levels of ability obtained by 8 high-skilled students require new procedures well in solving problems, 24 capable students are having difficulty in the process of problem transformation, and 4 low-ability students are unable to handle new procedures.Keywords: problem-solving ability, Newman's procedure